Evaluating the Oral Language Skills of English-Stream and French Immersion Students: Are the CLB/NCLC Applicable? - Burchell, Diana; Hipfner-Boucher, Kathleen; Selvachandran, Janani; Cleave, Patricia; Chen, Xi (Canadian Journal of Applied Linguistics / Revue canadienne de linguistique appliquée, 2020)
This study examined the oral language skills of grade-two anglophone children enrolled in French Immersion and English-stream programs. The study had two objectives: (a) to compare performance between the groups on measures of receptive vocabulary, narrative comprehension, and narrative production (i.e., structure and language) in English, and (b) to explore the applicability of the Canadian Language Benchmarks/Niveaux de compétences linguistiques canadiens (CLB/NCLC) to assessment of their conversational competency. All children (English-stream n = 27, French Immersion n = 33, aged 7-8 years) were tested in English. In addition, the French Immersion students were tested using equivalent measures in French. The results comparing performance in English revealed no differences between the groups on receptive vocabulary, narrative comprehension and narrative structure. However, the English-stream children outperformed their French Immersion peers in narrative language. Furthermore, CLB/NCLC listening and speaking criteria were applied to conversational samples yielding level scores in English (both groups) and French (French Immersion only). The range of benchmarks that are appropriate for this population is discussed in detail.